(Re)surfacing an exploration of the reverse mold method as applied in freeze casting to portray the void as the sculptural image of the desaparecidos - Sicat, Jose Manuel L.
The creative research captures the phenomenon of disembodiment of the victims of Enforced Disappearances in the country, desparecidos, by presenting hollowed-out, empties portrait bust-sculptures in frozen, consecrated water solutions. Seen through transparent surfaces, a reimagined space is presented by reversing the roles of postive and negative molds as a trace representation of the physical corporeal body in the realm of the void.The act of consecrating water through a participatory ritual performed with the families allows transcendence of meaning as a medium. Beyond physical attributes, the medium serves as a carrier of (found) memories that symbolizes personal thoughts, feelings and struggles attached to longing. Here, materiality is loose and indefinite; as fluid as the thoughts surrounding the state of desparecidos that linger towards the dialectic of certainty and uncertainty of life or death, of the precariousness of being here and nowhere. Consecrated water is allowed to flow into every crevice of the molds and frozen to become forms of the desparecidos, resurfaced. I used an alternative way of presenting the sculpture by combining new ways of approaching traditional techniques and processes in art, with borrowed methods in freezing and refrigeration in the field of science and technology. Consecrated water transposed as casting material that underwent temporal preservation through freezing connote the deeper meaning of suspended grief in memoriam offered by the families to their missing loved one. The amalgamation of these explorations is manifested in my creative outputs, presented through a tableau of selected desparecidos, depicting not only individual personas but also marginalized sectors in our society targeted, victimized by the injustice: youth, women, workers, peasants, teachers, and indigenous peoples. Through the creative production that involved the social process of consecrating, I aimed to bring to the public the issue of enforced disappearances, which gravely violates the rights of the desparecidos. I stand in solidarity with the families, friends, and human rights defendersas we altogether continue to seek justice. The themes in art that are present in the study are: History as in recorded cases of enforced disappearances from Martial Law period in the 1970s until 2012; Time as conveyed by the freezing and refrigeration technique, Body as represented by the consecrated water solutions; Space as seen in the absent, hollowed-out void of reverse casting; and finally, Identity as in the portrayal of each of the desparecidos.